Accelerometry as a tool for evaluating the efficacy of treatment with a green-lipped mussel extract in dogs with joint disease : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Biological Sciences at Massey University, Manawatū, New Zealand - Bolton, Samantha (Massey University, 2019)
Accelerometry is a useful objective measure of a dog’s daily activity, which is most commonly expressed simply as the raw activity count of a defined epoch such as a minute, hour, or day. The accelerometry data has potential as a tool to categorise a dog’s gait or estimate its speed of movement. Thus, accelerometry is a tool that can be used to monitor diseases that affect a dog’s activity, such as osteoarthritis. Osteoarthritis (OA) is the most frequently identified musculoskeletal disorder in dogs, with clinical signs including lameness, swelling, and pain. Although incurable, there are a variety of treatments that can reduce the clinical signs of OA, including green-lipped mussel (Perna canaliculus) extract (GLME), which has evidence of antiinflammatory activity. GLME can alleviate clinical signs such as swelling and pain, when given to dogs with OA. New Zealand farm dogs are highly active dogs with a high frequency of joint disease within the population. The level of management of joint disease in the population is low, thus they are a novel and potentially suitable population for trialling treatments of OA. Accelerometry is an obvious means of detecting an effect of treatment in these working dogs. Therefore, the principle aim of this thesis was to determine if New Zealand working farm dogs are a suitable study population, and if accelerometry is able to detect an effect of GLME nutraceuticals in this population of dogs with mild joint disease. In order to achieve that aim, it was decided to first determine if the chosen accelerometry system could estimate the speed, and characterise the gait of dogs. In the first trial, dogs (n=8) were exercised on a treadmill that was held at speeds that were comfortable for them to walk, trot, and run. Their gait was visually annotated using a motion capture system, and speed was determined from the treadmill. The association between the basic accelerometry output “delta-G”, and the dog’s speed and gait in 10 second intervals was tested. It was concluded that there was a delta-G threshold above which, the dogs would reliably be gaiting faster than a walk. However, the linear association between delta-G and speed was poor, and decreased with increasing speed. Thus, it was not possible to accurately predict speed using the accelerometry system. In the second trial, dogs (n=27) were treated with two dose strengths of a GLME nutraceutical and a placebo for 8 weeks each in a randomised, cross-over, double-blinded study. Linear mixed models were created to estimate the effect of treatment on delta-G, which was collected in 10 second epochs. Accelerometry was able to detect small, but significant effects in this population. In addition, it was concluded that treatment with GLME increased peak activity in working farm dogs with signs of joint disease, and increased night-time activity slightly. While joint disease is highly prevalent in NZ working farm dogs, there were significant problems and limitations that question the suitability of this population for further similar studies. Nonetheless, the research presented in this thesis suggests that farm dogs with signs of joint disease might benefit from treatment with the GLME used here, even when they are mildly affected.
Keywords: 300911 Veterinary pharmacology